Field testing of MOSAIMS@ - Mohd. Yousof, Mohd. Fairouz (2010)
Surge arrester is an important protection device installed mostly at the power transmission substation. It is used to safely channel through the overvoltage surge due to the lightning or switching effect to the ground and thus protecting the other vital power equipment at the substation. Ageing or degradation of the arrester is an important aspect to be concern with because the arrester may be due for replacement. Predictive maintenance should be conducted from time to time in order to monitor the degradation of the arrester and predict when to change the arrester before it fails. The leakage current that flows through the arrester during the normal condition can be measured easily using current probe, and its third harmonic resistive leakage current is directly related to the ageing of the arrester. Various methods were used to measure the third harmonic leakage current, among the latest is Modified Shifted Current Method (MSCM). This method has been applied to a newly developed portable device which is called the Metal Oxide Surge Arrester Intelligent Monitoring SYSTEM (MOSAIMS). MOSAIMS which is developed in the Institute of High Voltage and High Current (IVAT) has been through testing at the high voltage laboratory before and due to the lack of actual measurements at the power transmission substations, the performance of the MOSAIMS is still yet to be concluded. This project aims to thoroughly test the MOSAIMS especially to determine its accuracy on measuring the third harmonic resistive leakage current. The measurements from the MOSAIMS will be compared with the measurements using SCAR-10, a device which is used by the local power utility company. Finally, the report on the measurement accuracy of MOSAIMS and the possible future works in improving the MOSAIMS included.